Streaming Video Perfomance FDD Mode in Handover Process on LTE Network - Cornelis Frederik Junifer Latupapua; Tri Kuntoro Priyambodo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2018)
LTE networks were created to improve on previous technologies, where the advantages of LTE networks are at the speed of data transfer and greater service capacity, reduced operational costs and can be integrated with existing technologies.This simulation is used to analyze the video performance of FDD streaming mode in handover process using Network Simulator 3 with 3 cell for different speed and number of users, with delay, packet loss and throughput parameters. The test results show that the performance of streaming video in handover process on all test, not affected by delay value. The highest delay value is still in good category that is 153. 43 ms. The highest packet loss is 54.5% with 60 users at speeds of 100 km / h. The highest throughput value is 0.60 Mbps at a speed of 40 km / h with 5 users and the lowest throughput value is 0.40 Mbps at a speed of 60 km / h with 60 users. The best performance occurred at a speed of 40 km / h, on the contrary at speeds of 70 Km / h and 100 Km / h, the performance decreased due to increased packet loss and decreased throughput value.